Pendidikan Sebagai Langkah Menjaga Keutuhan Ciptaan Tuhan - Pintor Marihot Sitanggang; Jantua Tambunan; Ridho Kardo Parhusip (EDUKASIA Jurnal Pendidikan dan Pembelajaran, 2022)
The development of the world of education today is a proof of human existence as a creature created by God who has a higher degree and value than other creations. Intellect, mind, wisdom are more human values ​​than other creations, so that humans receive a mandate to control other creations to meet human needs. But it should be understood that the task of mastering it is also inseparable from the call to maintain and maintain the integrity, sustainability and preservation of God's other creations in this world. Through education, humans have been more enabled to understand and maintain values, functions, existence and qualities than other creations of God who are both in this world. This call is of course very closely related and mutually supportive with the call of the church to voice and accompany humans to maintain the integrity of God's creation in this world. A blend that complements and complements theology (Christianity and church teachings) with education in implementing the teachings of God's Word to maintain the integrity of the existence of God's creation in this world. So that what is voiced in God's Word at the event of creation that "God saw everything is good" can be maintained and continue in the midst of this world. Education shows its role and function as a step to maintain the integrity of God's creation.